COMPARISON OF IN VIVO CYANIDE EXAMINATION WITH PICRIC ACID AND PRUSIAN BLUE METHODS - Mardhatillah Marsa; Hendro Widagdo; Suhartini Suhartini (Syntax Corporation Indonesia, 2023)
This study aims to determine the comparison of invivo cyanide examination by comparing the Pyric Acid method with the Blue Prusian method in the stomachs of experimental animals. It is an imental expre research. Samples of 40 white Wistar rats weighed between 100-200 g. Then the 40 rats were given lethal dose cyanide orally and divided into 2 groups: 1 group will be detected cyanide by picric acid method and 1 other group using blue prusian method. In such groups are taken gastric tissue. Consecutive examination time intervals on days 1 and 7. The results of cyanide examination with the Picric Acid method were obtained on day 1 of positive gastric tissue cyanide 94.7%, while with the Blue Prusian method on day 1 examination positive cyanide 85%. The results of cyanide examination with the PikraAcid t method on day 7 found that the gastric tissue was positive for cyanide 36.8%, while with the Blue Prusian method 35%. Both methods showed high sensitivity to cyanide examination in the gastric postmortem (P<0.05).